A child with soft-tissue infection and lymphadenitis. (November 2020) - Froböse, N.J.; Masjosthusmann, K.; Huss, S.; Correa-Martinez, C.L.; Mellmann, A.; Schuler, F.; Kahl, B.C.; Wittkowski, H.; Schaumburg, F.
Abstract: We report a case of a soft-tissue infection with Francisella philomiragia, a rare opportunistic pathogen in individuals with chronic granulomatous disease.